(untitled) (Cultura Económica, 2019)
In this article the author compares market reforms effects carried out by the end of the last century in Argentina with the ones implemented in Mexico and Chile. In her view, in the Argentine case, market reforms were marked by serious difficulties because of the political-institutional context of the country, characterized by a lack of an export-oriented national strategy due to the State’s patrimonialist intervention by business and labor interests.